Surface Stability of Azobenzene‐Based Thin Films in Aqueous Environment: Light‐Controllable Underwater Blistering (Adv. Mater. Interfaces 9/2022). Issue 9 (23rd March 2022) - Audia, Biagio; Fedele, Chiara; Tone, Caterina M.; Cipparrone, Gabriella; Priimagi, Arri
Abstract : Surface Stability of Azobenzene‐Based Thin Films in Aqueous Environment In article number 2102125 by Biagio Audia, Arri Priimagi, and co‐workers, the morphological stability of azobenzene‐based film surface is tested in aqueous environment and a water‐induced blistering instability is revealed. A blisters formation mechanism derived by the experimental observations is proposed. Additionally, simple routes for preventing the phenomenon are indicated, and photocontrol over the blisters orientation and onset is demonstrated.